HBoV-1: virus structure, genomic features, life cycle, pathogenesis, epidemiology, diagnosis and clinical manifestations - Mohammadi, Mehrdad (Frontiers in Cellular and Infection Microbiology, 2023)
The single-stranded DNA virus known as human bocavirus 1 (HBoV-1) is an icosahedral, linear member of the Parvoviridae family. In 2005, it was discovered in nasopharyngeal samples taken from kids who had respiratory tract illnesses. The HBoV genome is 4.7–5.7 kb in total length. The HBoV genome comprises three open-reading frames (ORF1, ORF2, and ORF3) that express structural proteins (VP1, VP2, and VP3), viral non-coding RNA, and non-structural proteins (NS1, NS1-70, NS2, NS3, and NP1) (BocaSR). The NS1 and NP1 are crucial for viral DNA replication and are substantially conserved proteins. Replication of the HBoV-1 genome in non-dividing, polarized airway epithelial cells. In vitro, HBoV-1 infects human airway epithelial cells that are strongly differentiated or polarized. Young children who have HBoV-1 are at risk for developing a wide range of respiratory illnesses, such as the common cold, acute otitis media, pneumonia, and bronchiolitis. The most common clinical symptoms are wheezing, coughing, dyspnea, and rhinorrhea. After infection, HBoV-1 DNA can continue to be present in airway secretions for months. The prevalence of coinfections is considerable, and the clinical symptoms can be more severe than those linked to mono-infections. HBoV-1 is frequently detected in combination with other pathogens in various reports. The fecal-oral and respiratory pathways are more likely to be used for HBoV-1 transmission. HBoV-1 is endemic; it tends to peak in the winter and spring. This Review summarizes the knowledge on HBoV-1.